THE ICONOCLASM ON MODERN KNOWLEDGE SYSTEM REGIME IN BOB DYLANâS âONE MORE CUP OF COFFEE (TO THE VALLEY BELOWâ): A NARRATOLOGY AND DECONSTRUCTIVE STUDYâ - saputra, imam hendra (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2017)
The bestowal of Nobel Prize 2016 in Literature for having created new poetic expressions within the great American song tradition to Bob Dylan indicated that the understanding of literature in post-modern world has begun to permeate its traditional boundary of definition.The research will deploy textual analysis approach with the focus to narratology, with conclusion base on deductive analysis on the holistic data relation. The data collecting method initiates mostly with close reading. Subsequently, those data are divided, arrange and grouped to certain criteria that support the process of analysis.Dylanâs âOne More Cup of Coffee (To the Valley Belowâ) uniquely identifies the conventional knowledge as something that is not ultimate, instead it identifies it as something that has the value of truth which may be rivaled by other kind of system of truth. The plural existence of system of knowledge is not only acknowledge as juxtaposed entities, but even furthermore deconstructed to be something that successfully find the true essence of truth does not found in conventional system of knowledge.